Muslim modernities expressions of the civil imagination - Sajoo, Amyn B. (I.B. Taurus, 2008)
How does Islam engage with the idea of the modern and with the contemporary world? How is Muslim tradition to be reconciled with a world in continuous flux and change? These questions lie at the heart of current discussions of the Islamic faith and of its doctrines, beliefs and practices. Engaging directly with such questions, this important volume discusses such key themes as identity and citizenship, piety and protest and music and modes of dress. Muslim as well as non-Muslim scholars explore how religiosity and tradition may both have an active role to play in the unfolding of what we under.